an Analysis Morpheme in Smoking Article - Ilham Rizki; Zakrimal Zakrimal (Linguistic, English Education and Art (LEEA) Journal, 2020)
The aimed of the research were to find out the type of morpheme of morphology on Smoking article. It was descriptive qualitative research. In collecting the data the research applied observational method and non-participatory technique. The data analyzed used the theory of Bauer. The writer applied the words in the article as the data. It was found the 20 words of morphology. In this research focus in analyzing words in the article proposed theory of Bauer about type of morpheme. The words are shorten, smoker, drugs, dependent, safer, cooled, additional, antifreeze, responsible, fertility, performance, circulation, illness, properly, smokeless, pressure, information, organization, helpful, hardest.The writer found 20 data in this article entitled Smoking. Data found are words that have their own meanings. The data changes meaning and grammar after adding Suffix and Affix. Researcher research this issue to make reader can understand the process making a word. Keywords: Morphology, Morpheme, Derivational, Inflectional.